2017
DOI: 10.1007/s11596-017-1788-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment outcomes of ticagrelor and clopidogrel among patients undergoing percutaneous coronary intervention: A meta-analysis

Abstract: We performed a meta-analysis of randomized controlled trials (RCTs) to investigate the efficacy and safety of ticagrelor (TIC) vs. clopidogrel (CLO) in patients undergoing percutaneous coronary intervention (PCI). In Jun 2016, a literature search was started and all the studies were conducted from 2010 to 2015. We systematically searched the literature through the MEDLINE database, Cochrane library, and EMBASE database. Quality assessments were evaluated with Jadad quality scale. Data were extracted considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
7
0
2
Order By: Relevance
“…In this study, we found no statistically significant difference in the risk of a major or minor bleeding in patients exposed to ticagrelor compared to clopidogrel. This was consistent with the findings of a previous meta-analysis in younger patients which showed that major and minor bleeding events did not differ with either ticagrelor or clopidogrel [36] . However, this finding needs to be interpreted with caution.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found no statistically significant difference in the risk of a major or minor bleeding in patients exposed to ticagrelor compared to clopidogrel. This was consistent with the findings of a previous meta-analysis in younger patients which showed that major and minor bleeding events did not differ with either ticagrelor or clopidogrel [36] . However, this finding needs to be interpreted with caution.…”
Section: Discussionsupporting
confidence: 92%
“…This was consistent with the findings of a previous meta-analysis in younger patients which showed that major and minor bleeding events did not differ with either ticagrelor or clopidogrel. [36] However, this finding needs to be interpreted with caution. All the various studies included in this review had varying definitions for major and minor bleeding.…”
Section: Discussionmentioning
confidence: 91%
“…A recently published meta-analysis showed that major and minor bleeding events were not significantly different with either ticagrelor or clopidogrel. [ 32 ] Nevertheless, the study involved only 6 trials and included only studies which were published between the years 2010 and 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Son birkaç yılda antikoagulan, antitrombositik ve antilipidemik ilaç gruplarında, mevcut tedavilere alternatif olarak yeni ajanlar geliştirilmiştir [1][2][3] . Birçok ülkede bu yeni ilaçların reçetelenme oranındaki artış, gebeliğinin farkında olmadan bu ajanları kullanan kadın hastaların ve neticesinde fetüsün ilaçlara istenmeden maruz kalması konusunu gündeme getirmektedir.…”
Section: Introductionunclassified
“…Ayrıca maternal maruziyetin olduğu gestasyonel dönem ve kullanılan ilacın dozu da fetal risk analizi yapılırken göz önüne alınmalıdır. Zira gebeliğin 3-8. haftalar arasında olan organogenezis dönemi maternal ilaç maruziyetlerinin fetüste potansiyel teratojenik etki yapabileceği gebelik dönemi olarak bilinmektedir 2,3 .…”
Section: Introductionunclassified